The COVID-19 Vaccination: Realization on Halal Vaccines for Benefits - Sholeh, M Asrorun Niam; Helmi, Muhammad Ishar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
Vaccination is one of the alternatives that has been found to overcome the COVID-19 outbreak. The long-awaited discovery of its reality remains a debate among the public. Various issues continue to emerge, both health-based and religious-based. The refusal is wrapped by questions related to doubts about treatment with vaccination or the halalness of vaccine products. MUI as an institution that is trusted by the public in determining the results of its ijtihad, issues a fatwa number 2 of 2021 concerning vaccines. This paper will conduct related studies regarding the permissibility of using the COVID-19 vaccine from the perspective of fiqh and applicable laws in Indonesia. This study uses a normative legal research method with a rule of law approach and a doctrinal approach, In addition, the data obtained by library research. The results of this study explain that the vaccines used are of course required to use halal and holy vaccines. However, immunization with haram and/or unclean vaccines can be permitted under several conditions, namely when used in an emergency; halal and holy vaccine ingredients have not been found, and there is information from competent and trusted medical personnel that there is no halal vaccine.